1986
DOI: 10.1246/bcsj.59.1341
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Synthesis of Cyclopropanecarboxylic Acid Derivatives by the Ni(CO)4-Induced Reductive Carbonylation Reaction of gem-Dibromocyclopropanes

Abstract: Reductive carbonylation of gem-dibromocyclopropanes was achieved by treatment with tetracarbonylnickel in the presence of alcohols, amines, thiols, or imidazole in DMF leading to the corresponding cyclopropanecarboxylic acid derivatives, respectively. Use of disulfides as an initial nucleophile resulted in carbonylation with sulfenylation at the geminal position. This method was applied to the intramolecular reductive carbonylation reaction of 2,2-dibromocyclopropanealkanols into bicyclic lactones. Nickel carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Cyclopropane and its derivatives are reactive, versatile compounds that can be found throughout nature . They are important throughout biology and can be synthesized and utilized for many important reactions. , Structural information on these types of molecules is important to obtain to understand the chemistry and reactivity behind these enzymatic processes in biology or reactions performed in the lab. Infrared, Raman, microwave, and X-ray crystal structure studies have been reported previously for cyclopropanecarboxylic acid (CPCA). To obtain a more accurate gas-phase structure, transitions from 13 C singly substituted isotopologues were needed to continue from the previous work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopropane and its derivatives are reactive, versatile compounds that can be found throughout nature . They are important throughout biology and can be synthesized and utilized for many important reactions. , Structural information on these types of molecules is important to obtain to understand the chemistry and reactivity behind these enzymatic processes in biology or reactions performed in the lab. Infrared, Raman, microwave, and X-ray crystal structure studies have been reported previously for cyclopropanecarboxylic acid (CPCA). To obtain a more accurate gas-phase structure, transitions from 13 C singly substituted isotopologues were needed to continue from the previous work.…”
Section: Introductionmentioning
confidence: 99%
“…1 They are important throughout biology 2 and can be synthesized and utilized for many important reactions. 3,4 Structural information on these types of molecules is important to obtain to understand the chemistry and reactivity behind these enzymatic processes in biology or reactions performed in the lab. Infrared, Raman, microwave, and X-ray crystal structure studies have been reported previously for cyclopropanecarboxylic acid (CPCA).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the known reactions of this type (Scheme , eq 3) are either nonselective due to harsh reaction conditions or have no potential selectivity issue, with only a handful of examples showing good site or facial differentiation in polycyclic substrates, where selectivity of addition is imparted by excessive rigidity and bulk . The same challenge exists , in the formal substitution of cyclopropyl halides with thiolates en route to stereochemically defined cyclopropyl sulfides . Herein, we report a full account on the formal nucleophilic substitution of bromocyclopropanes applicable to a wide range of oxygen- and sulfur-based nucleophiles, with efficient selectivity control achieved by three alternative means: sterics, directing effect, and thermodynamic equilibrium …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cyclopropanecarboxylic acid (CPCA) is an important biologically active compound due to the hypoglycemic metabolic effects shown in experiments by Duncombe and Rising in several animal species, including humans 2 . CPCA can synthesized using chiral copper carbenoids 3 and due to the versatility of the cyclopropane ring, geminal dihalides of CPCA can be easily derivatized using a Ni induced reductive carbonylation 4 . Other syntheses of CPCA utilize other transition metal catalyzed reactions, cycloaddition of alkenes, sulfoxides and other metal carbenoids 1 .…”
Section: Introductionmentioning
confidence: 99%